2021
DOI: 10.3389/fimmu.2021.711231
|View full text |Cite
|
Sign up to set email alerts
|

A History of Endometriosis Is Associated With Decreased Peripheral NK Cytotoxicity and Increased Infiltration of Uterine CD68+ Macrophages

Abstract: Women with endometriosis may have a defective immune system. However, evidence of the immune responses of endometriosis patients with a history of endometriosis surgery is lacking, and the association between the location of endometriosis lesions and immune responses is unclear. This retrospective study included 117 females with reproductive failure and a history of endometriosis and 200 females with reproductive failure but without endometriosis to analyze their endometrial and peripheral immune responses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Macrophage infiltration of ovarian endometriomas has been previously reported [ 24 ]. Furthermore, we have shown in a mouse model of endometriosis that progression of ENDO in ectopic lesions with high fat diet was associated with increased localization of macrophages in stromal cells as measured by F/480 immunostaning [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage infiltration of ovarian endometriomas has been previously reported [ 24 ]. Furthermore, we have shown in a mouse model of endometriosis that progression of ENDO in ectopic lesions with high fat diet was associated with increased localization of macrophages in stromal cells as measured by F/480 immunostaning [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These patients included 22 females with a history of RIF who experienced failed pregnancy in the next period after endometrial scratch and 19 fertile females who retrieved successful pregnancy in the next period after endometrial scratch. Herein, RIF was defined as women who experienced two or more retrieval cycles and transferred more than ten high-quality embryos without pregnancy ( 29 ). Among these patients, endometria from six RIF patients and six controls were subjected to proteomics analysis using isobaric tags for relative and absolute quantification (iTRAQ).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are different results regarding changes in the number of peripheral NK cells in endometriosis, it is unanimously agreed that peripheral NK cells have strong cytotoxicity; however, this effect is weakened in endometriosis. Research has shown that peripheral NK cytotoxicity is significantly decreased in endometriosis patients [ 32 ]. Oosterlynck et al observed a decrease in the cytotoxic activity of peripheral NK cells in patients with stage I/II endometriosis as the disease progressed.…”
Section: The Proportion Phenotype and Function Of Nk Cells In Normal ...mentioning
confidence: 99%